A Novel Two-Stage Approach for Nonlinearity Correction of Frequency-Modulated Continuous-Wave Laser Ranging Combining Data-Driven and Principle-Based Strategies - Shichang Xu; Guohui Yuan; Hongwei Zhang; Chunyu Hou; Zhirong Li; Pansong Zhang; Wenhao Xu; Zhuoran Wang (Photonics)
The frequency linearity of a frequency-swept light signal is critical for ensuring the precision of Frequency-Modulated Continuous-Wave (FMCW) laser ranging systems. A two-stage nonlinearity correction mechanism for frequency-swept light is proposed, combining both data-driven and principle-based approaches. In the main correction stage utilizing an electro-optic phase-locked loop (EO-PLL), high temporal resolution phase detection is achieved. To address the failure of the EO-PLL caused by a bandwidth limitation of the digital loop filter (DLF), a novel pre-correction mechanism is developed based on a data-driven approach. In this mechanism, the neural network (NN) model establishes a mapping relationship between the input and output of the real laser-modulation system, which effectively simulates this physical system and avoids the risk of trial-and-error damage. Afterwards, the Soft Actor–Critic (SAC) model interacts with the NN model and trains a decision-making agent to determine the optimal modulation strategy for the nonlinearity pre-correction of the frequency-swept light. During the training process of the SAC agent, both the modulation strategy and the accuracy of evaluating the strategy’s effectiveness are optimized. Moreover, in contrast to the basic Actor–Critic model, the SAC model enhances the exploration of modulation possibilities by maximizing entropy expectation of random strategy, thereby improving the robustness of the pre-correction mechanism. Finally, the frequency-swept characteristic analysis experiment proves that integrating NN-SAC with EO-PLL enables frequency locking under the reduced bandwidth of the DLF. Additionally, through actual ranging experiments, it is also demonstrated that the proposed mechanism significantly enhances ranging precision, repeatability, and stability. Therefore, by integrating data-driven and principle-based approaches, this investigation offers an innovative perspective for the nonlinearity correction of FMCW laser ranging and, furthermore, electro-optic control scenarios.